Pengaruh Lingkungan Keluarga Dan Keaktifan Organisasi Terhadap Prestasi Akademik Mahasiswa - Nia Rosita; Nurkhojin Nurkhojin; Khalid Iskandar (JURNAL RISET MANAJEMEN (JURMA), 2023)
This study aims to determine the influence of the family environment and activeness in the organization on the academic achievement of study students at the Hima of the Faculty of Economics, Muhadi Setiabudi University. This research uses explanatory research with quantitative methods. The technique used in this study used a saturated sampling technique with active student respondents participating in the Student Association of the Faculty of Economics and Business, Muhadi Setiabudi University. totaling 50 students. The data collection technique used a questionnaire, the analytical method used was multiple linear regression.The results of this study show that: 1) Students who are active in participating in HIMA are in the category of high academic achievement as much as 62%, those who fall into the moderate category are as much as 32%, and those who fall into the less category are as much as 6%. 2) There is a positive and significant influence of the family environment on academic achievement. There is a positive and significant influence of activeness in the organization on academic achievement. There is a positive and significant influence of family environment and activeness in organizations on academic achievement.